Teachers’ strategies on teaching grammar: Facts and expectations of senior high school teachers at Ambon - Threesje Roza Souisa; Lelyemin Yanuarius (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study is aimed at describing the English as a Foreign Language (EFL) senior high schools’ teachers’ perceptions on grammar teaching; their teaching strategies which are the most and less frequently applied in their classroom practices and the challenges that they have in teaching grammar. Explanatory mixed approaches were conducted involving 63 teachers as the sample population in collecting quantitative data, and five selected teachers as participants for collecting the qualitative data. The findings showed that teachers' perceptions of grammar teaching are based on their conceptual knowledge as they have experienced it and it is based on grammar theories. The teachers applied vary grammar approaches and strategies but they still face with the challenges in teaching grammar such as students' learning styles and less of teaching references.